Automation control theory perspectives in intelligent systems. proceedings of the 5th Computer Science On-line Conference 2016 (CSOC2016) /: proceedings of the 5th Computer Science On-line Conference 2016 (CSOC2016). Vol 3 : (2016) - Unknown
No abstract available